The identity of the sport psychology profession: A multinational perspective. (May 2022) - Quartiroli, Alessandro; Wagstaff, Christopher R.D.; Hunter, Heather; Martin, Daniel R.F.
Abstract: Objective: To ensure public safety, duty of care, and professional advancement, there is a need for scholars to explore factors that impact the professional experiences of sport psychology professionals (SPPs). One such factor is professional identity, which has been shown to positively contribute to an enhanced sense of legitimacy of the profession in the eye of the public and sport stakeholders (i.e., athletes, coaches, sport scientists, administrators) and to positively impact the experience and effectiveness of practitioners. Yet, little research has directly examined the construct of professional identity within sport psychology, with this oversight posing a risk to the future of the profession. Design: This interview-based study was situated within critical realism. We conducted a qualitative study using semi-structured interviews to explore the understanding and perceptions and experiences of the professional identity among SPPs. Methods: Following theoretical criterion-based sampling, we interviewed 33 expert ( n  = 13), experienced ( n  = 12), and early career ( n  = 8) SPPs regarding their views on PI. The nationalities of these SPPs (male n  = 16; female n  = 17) represented sixteen different countries on four different continents. Results: Data were analyzed using reflexive thematic analysis and showed a relatively shared meaning of professional identity which unfolded across the career span. Moreover, the professionals in this study seemed to identify their pride for and their knowledge of the profession as key factors in the development of their PI. Furthermore, they identified how their professional role, expertise, and interactions with other professionals within the field played an important role in sustaining a professional identity. Conclusion: We interpreted the interview data as supporting the importance of professional identity for SPPs and consider the contribution of this within a developmental framework for effective practice. Highlights: A sport psychology professional identity can contribute to legitimizing the profession. Sport psychology professionals share common factors that foster their professional identity. An individual's sport psychology professional identity is constantly evolving. Professionals highlight the importance of professional identity in the development of their careers.